Assessment of the clinical significance of serum matrix metalloproteinases MMP-2 and MMP-9 in patients with various chronic liver diseases and hepatocellular carcinoma - Kuyvenhoven, Johan Ph.; van Hoek, Bart; Blom, Eric; van Duijn, Wim; Hanemaaijer, Roeland; Verheijen, Jan H.; Lamers, Cornelis B.H.W.; Verspaget, Hein W. (Thrombosis and Haemostasis, 2003)
Matrix metalloproteinases (MMPs) have the ability to degrade basement membranes and may thus play an important role in extracellular matrix turnover in liver fibrosis and carcinogene-sis. Serum levels of MMPs have been suggested as diagnostic markers in these processes.We measured serum MMP-2 and MMP-9 by ELISA in 91 patients with chronic liver disease, including 25 patients with hepatocellular carcinoma (HCC), and in 60 controls.MMP-2 was significantly higher in patients with chronic liver disease compared to controls, and increased with Child-Pugh class. There was a significant correlation between MMP-2 and liver function (bilirubin, albumin, and prothrombin time), and a strong opposite correlation between MMP-9 and these parameters.MMP-2 levels in patients with HCC were significantly higher than in controls, but comparable to patients with chronic liver disease without this malignancy. MMP-9 yielded no significant differences between patients with or without HCC and controls.Serum MMP-2 and to a lesser extent MMP-9 correlate with the severity of liver disease and may reflect changes in extracellular matrix remodeling. Due to a considerable overlap in patients with chronic liver disease with or without HCC, MMP-2 and MMP-9 can not be used as a diagnostic marker for HCC.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Hepatocellular carcinoma; liver disease; matrix metalloproteinases